Face Processing and Social Functioning in Pediatric Brain Tumor Survivors. (27th July 2021) - Hocking, Matthew C; Albee, May; Brodsky, Cole; Shabason, Emily; Wang, Leah; Schultz, Robert T; Herrington, John
Abstract: Objective: Pediatric brain tumor survivors (PBTS) experience deficits in social functioning. Facial expression and identity recognition are key components of social information processing and are widely studied as an index of social difficulties in youth with autism spectrum disorder (ASD) and other neurodevelopmental conditions. This study evaluated facial expression and identity recognition among PBTS, youth with ASD, and typically developing (TD) youth, and the associations between these face processing skills and social impairments. Methods: PBTS ( N = 54; ages 7–16) who completed treatment at least 2 years prior were matched with TD ( N = 43) youth and youth with ASD ( N = 55) based on sex and IQ. Parents completed a measure of social impairments and youth completed a measure of facial expression and identity recognition. Results: Groups significantly differed on social impairments ( p < .001), with youth with ASD scoring highest followed by PBTS and lastly TD youth. Youth with ASD performed significantly worse on the two measures of facial processing, while TD youth and PBTS were not statistically different. The association of facial expression recognition and social impairments was moderated by group, such that PBTS with higher levels of social impairment performed worse on the expression task compared to TD and ASD groups ( p < .01, η 2 = 0.07). Conclusions: Variability in face processing may be uniquely important to the social challenges of PBTS compared to other neurodevelopmental populations. Future directions include prospectively examining associations between facial expression recognition and social difficulties in PBTS and face processing training as an intervention for PBTS.